Environment investment through Work for Taxes - Villanueva Caceres, Gabriela (2023)
The Environmental Authority has identified the existence of millions of hectares of degraded ecosystems that provide ecosystem services that need to be recovered. This problem constitutes a natural infrastructure gap that must be addressed by the authorities to establish actions that promote investments in natural protection. An alternative to reduce this gap is the application of the Works for Taxes mechanism. This is a public investment execution modality that allows to have quality infrastructure and services in an agile way through the cooperation of the public and private sectors. Implemented since 2009, it operates successfully, contributing to the closing of priority infrastructure and services gaps at the national level. However, it is not usually used for the implementation of environmental investments. Therefore, this article analyzes the potential of the application of Works for Taxes as a mechanism to close environmental infrastructure gaps.